Insertional Achilles tendinopathy: Causes, diagnosis, and treatment - Zambelli, Roberto; Simões Castilho, Rodrigo; Brandão Magalhães, João Murilo; Almeida Taveira de Souza, Matheus Levy; Costa Machado, Paula; Bertani Dressler, Hugo (Journal of the Foot & Ankle, 2026)
Insertional Achilles tendinopathy (IAT) is a multifactorial condition characterized by degeneration at the tendon-bone interface, leading to chronic heel pain, stiffness, and functional impairment. This review explores etiopathogenesis, clinical presentation, diagnostic strategies, and both conservative and surgical treatments for IAT. Risk factors include mechanical overload, aging, metabolic disorders, and biomechanical abnormalities. Diagnosis is primarily clinical, supported by imaging modalities such as ultrasound and magnetic resonance imaging, although imaging severity may not correlate with symptoms. Initial management emphasizes non-surgical options, including eccentric exercises, footwear modifications, and extracorporeal shockwave therapy, which have shown promising outcomes in symptom reduction and functional improvement. Injectable therapies—particularly hyaluronic acid and platelet-rich plasma—have emerged as potential adjuncts, though further evidence is needed to validate their efficacy and define ideal protocols. Surgical interventions are considered in refractory cases and include open debridement, calcaneoplasty, tendon reattachment with or without flexor hallucis longus transfer, and minimally invasive techniques. The choice of approach depends on the extent of tendon degeneration, anatomical considerations, and patient-specific factors such as activity level and comorbidities. Minimally invasive procedures, including percutaneous calcaneoplasty and Zadek osteotomy, offer reduced complication rates and faster recovery, especially in selected patients. Outcomes are generally favorable across techniques when all pathological components are addressed. However, complications such as wound healing issues and nerve injuries remain concerns. The review underscores the need for individualized treatment strategies and further high-quality studies to optimize IAT management and establish standardized therapeutic algorithms. Level of evidence I.